2019
DOI: 10.3847/1538-4357/ab5846
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Temperature Components of the Hot Circumgalactic Medium of the Milky Way

Abstract: We present a deep XMM-Newton observation of the Galactic halo emission in the direction of the blazar 1ES 1553+113. In order to extract the Galactic halo component from the diffuse soft X-ray emission spectrum, accurately modeling the foreground components is crucial. Here we present complex modeling of the foregrounds with unprecedented details. A careful analysis of the spectrum yields two temperature components of the halo gas (T em 1 = 10 6.32 K, T em 2 = 10 6.82 K). We find that these temperatures obtaine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 50 publications
(86 reference statements)
8
29
1
Order By: Relevance
“…Moreover, it agrees with previous indications that the missing baryons are likely significantly correlated with galaxies and groups (e.g. Nicastro et al 2018;Lim et al 2020;Das et al 2019Das et al , 2020.…”
Section: Quantitative Comparison In the Sdss Footprintsupporting
confidence: 91%
“…Moreover, it agrees with previous indications that the missing baryons are likely significantly correlated with galaxies and groups (e.g. Nicastro et al 2018;Lim et al 2020;Das et al 2019Das et al , 2020.…”
Section: Quantitative Comparison In the Sdss Footprintsupporting
confidence: 91%
“…The SDXB spectrum is usually described by a three-component model consisting of: 1) a foreground component of LB and SWCX, modeled as an unabsorbed thermal plasma emission in CIE, 2) a background component of CXB modeled with an absorbed power-law, and 3) the MW halo emission, modeled as an equilibrium thermal plasma absorbed by the cold gas in the Galactic disk (the halo emission toward the Galactic center is dominated by the bubbles; [1]). Recently we found that in few observations an additional absorbed thermal component and/or enhanced Ne abundance is required to explain the excess emission near 0.7 − 0.9 keV in the Suzaku [11] and XMM-Newton [10] SDXB spectra.…”
Section: Spectral Analysismentioning
confidence: 99%
“…Gatuzz & Churazov (2018) studied Ne ix absorption alongside O vii and O viii, focussing on the hot CGM and the ISM. The Milky Way CGM has also been probed with soft X-ray emission (e.g., Kuntz & Snowden 2000;Miller & Bregman 2015;Das et al 2019), and studied using combinations of emission and absorption (e.g., Bregman & Lloyd-Davies 2007;Gupta et al 2014;Miller & Bregman 2015;Gupta et al 2017;Das et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Another exception is the Milky Way. The halo of our own Galaxy has been studied using X-ray line emission, often in combination with X-ray absorption lines (e.g., Bregman & Lloyd-Davies 2007;Gupta et al 2014;Miller & Bregman 2015;Das et al 2019). Other studies focussed on absorption lines (e.g., Kuntz & Snowden 2000;Hodges-Kluck et al 2016;Gatuzz & Churazov 2018).…”
Section: Introductionmentioning
confidence: 99%